2018
DOI: 10.1074/jbc.ra118.002012
|View full text |Cite
|
Sign up to set email alerts
|

Global loss of leucine carboxyl methyltransferase-1 causes severe defects in fetal liver hematopoiesis

Abstract: Leucine carboxyl methyltransferase-1 (LCMT-1) methylates the C-terminal leucine α-carboxyl group of the catalytic subunits of the protein phosphatase 2A (PP2A) subfamily of protein phosphatases, PP2Ac, PP4c, and PP6c. LCMT-1 differentially regulates the formation and function of a subset of the heterotrimeric complexes that PP2A and PP4 form with their regulatory subunits. Global LCMT-1 knockout causes embryonic lethality in mice, but LCMT-1 function in development is unknown. In this study, we analyzed the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…It was already reported that deletion of LCMT-1 in mouse embryonic fibroblasts decreases methylation of PP2A C by >95%, methylation of PP4 C by ~93%, and methylation of PP6 C by ~87% (28). Furthermore, deletion of LCMT-1 in mammalian cells, or of its ortholog (PPM1) in yeast, reduces the formation of PP2A C/A/B heterotrimers, impairs catalytic activity, and reduces the steady-state abundance of the PP2A B, A, and C subunits (10)(11)(12)(13).…”
Section: D6 Methylation Sensitivity Is the Source Of A Detection Biamentioning
confidence: 99%
See 1 more Smart Citation
“…It was already reported that deletion of LCMT-1 in mouse embryonic fibroblasts decreases methylation of PP2A C by >95%, methylation of PP4 C by ~93%, and methylation of PP6 C by ~87% (28). Furthermore, deletion of LCMT-1 in mammalian cells, or of its ortholog (PPM1) in yeast, reduces the formation of PP2A C/A/B heterotrimers, impairs catalytic activity, and reduces the steady-state abundance of the PP2A B, A, and C subunits (10)(11)(12)(13).…”
Section: D6 Methylation Sensitivity Is the Source Of A Detection Biamentioning
confidence: 99%
“…The major function of PP2A C carboxyl methylation is thought to be the stimulation of PP2A activity and the promotion of PP2A heterotrimeric complex assembly (8)(9)(10)(11)(12). For example, methylation is required for formation of B subunitcontaining heterotrimers in mammalian cells (13). Methylation similarly facilitates mammalian B′ (B56) and B″ (PR72) trimer assembly in cells, although it does not seem to be strictly required for complex assembly in vitro (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…PP2AC-LCMT interactions were verified in Leishmania by immunoprecipitation of the two coexpressing tagged versions of the proteins. In contrast to Leishmania , LCMT is essential in mice (44). Overexpression of LCMT produces SNF resistance (Table 1), but its inactivation produced even more resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, leucine carboxyl methyltransferase (LCMT-1)-mediated carboxyl methylation of PP4C is required for the formation of PP4-PP4R1 holoenzyme; and methylation of PP2A is required for the formation of PP2A holoenzyme containing Bα and Bβ-type regulatory subunits 34,35 . Loss of LCMT-1 reduces PP2A holoenzyme formation and causes severe defects in fetal hematopoiesis and, consequently, embryonic lethality in mice 36 . We speculate that the modification of a phosphatase regulatory subunit is more likely to regulate a more defined subset of substrates, thereby impacting specific signaling pathway(s).…”
Section: Discussionmentioning
confidence: 99%